Algebraic Thinking in Problem-Solving: A Bibliometric Analysis - Luthfiana Tarida; Dedeh Suryani (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
Generalization and symbolic manipulation are fundamental components of algebraic thinking. Generalization is often regarded as the core of mathematics and a defining characteristic of problem solving. Consequently, the use of problem-solving contexts has strong potential to enhance and develop individuals’ algebraic thinking skills. Both algebraic thinking and problem solving play a crucial role in determining success in solving mathematical problems. To examine research trends in these areas, a bibliometric analysis was employed within a systematic mapping study by reviewing documents indexed in the Scopus database. The results indicate that between 2001 and 2021, only 35 Scopus-indexed articles explicitly addressed algebraic thinking and problem solving. This study aims to fill gaps in the state of the art by conducting a bibliometric review of these 35 articles. The findings reveal that algebraic thinking and problem solving remain prominent and relevant research topics in mathematics education. However, word cloud analysis shows that the term belief appears in relatively small proportions, while self-efficacy has not yet emerged within the thematic networks or research trends related to algebraic thinking and problem solving. Moreover, studies integrating algebraic thinking, problem solving, scaffolding, and self-efficacy are still limited. Research focusing on student participants and mathematical content within the maritime domain is also scarce. Therefore, a promising direction for future research is to explore algebraic thinking processes through problem-solving scaffolding based on levels of self-efficacy among maritime students.